Mixed legal systems, east and west - Palmer, Vernon V.; Maṭar, Muḥammad Yaḥyá; Koppel, Anna (Juris diversitas., 2015)
This book takes us far beyond the usual focus of comparative law with analysis of a broad range of jurisdictions, including mixtures of common and civil law, and also those mixing Islamic and/or traditional legal systems with those derived from common and/or civil law traditions. The discussion is situated within the broader context of the continuing tides of globalization, the emergence of Islamic governments in some parts of the Middle East, the calls for a legal status for Islamic law in some European countries, and the increasing focus on traditional and customary norms of governance in po.